Physical activity alters limb bone structure but not entheseal morphology. Issue 107 (June 2017) - Wallace, Ian J.; Winchester, Julia M.; Su, Anne; Boyer, Doug M.; Konow, Nicolai
Abstract: Studies of ancient human skeletal remains frequently proceed from the assumption that individuals with robust limb bones and/or rugose, hypertrophic entheses can be inferred to have been highly physically active during life. Here, we experimentally test this assumption by measuring the effects of exercise on limb bone structure and entheseal morphology in turkeys. Growing females were either treated with a treadmill-running regimen for 10 weeks or served as controls. After the experiment, femoral cortical and trabecular bone structure were quantified with μCT in the mid-diaphysis and distal epiphysis, respectively, and entheseal morphology was quantified in the lateral epicondyle. The results indicate that elevated levels of physical activity affect limb bone structure but not entheseal morphology. Specifically, animals subjected to exercise displayed enhanced diaphyseal and trabecular bone architecture relative to controls, but no significant difference was detected between experimental groups in entheseal surface topography. These findings suggest that diaphyseal and trabecular structure are more reliable proxies than entheseal morphology for inferring ancient human physical activity levels from skeletal remains.